The role of destination attributes and memorable tourism experience in understanding tourist revisit intentions - Mahdzar, Mazlina; Shuib, Ahmad; Ramachandran, Sridar; Mohammad Afandi, Syamsul Herman (IDOSI Publications, 2015)
The objective of this study is to examine the influence of destination attributes, memorable tourism experience and revisit intentions in Mulu National Park, Malaysia. A convenient sampling technique was used to select the sample. A total of 349 questionnaires were distributed to tourists at Mulu National Airport and were returned. The result from the finding suggests that tourists who have higher perceptions of the destination attributes of Mulu National Park are more likely to have positive memorable tourism experience, increasing behavioural intentions to revisit. Therefore, national parks need to pay attention to provide customers with unique experiences in order to elicit positive memorable tourism experience and ensure their relationship with customer through repeat visitation.